FORMULASI SEDIAAN EMULGEL EKSTRAK DAUN UNGU DENGAN PENAMBAHAN BIOENHANCER EKSTRAK LIDAH BUAYA - Asri Wulandari; Erni Rustiani; Septia Andini; Daniel Sinaga (Faculty of Pharmacy, Universitas Muslim Indonesia, 2023)
Purple leaves contain flavonoids as anti-inflammatory. Aloe vera contains lignin compounds as bioenchancers. Utilization of these two plants in the form of topical emulgel preparations with the hope of being able to reach the systemic circulation. This study aims to formulate purple leaf extract and aloe vera extract in the form of an emulgel. The formula was made in 4 variations with concentrations of aloe vera extract F0 (0%), F1 (2.5%), F2 (3%), F3 (3.5%). Quality parameters include organoleptic, pH, spreadability, viscosity, cycling test, and penetration test using cell diffusion method franz. The results showed that the aloe vera extract emulgel formulation had good physical quality, namely organoleptic viscous green color, characteristic aromatic odor, pH 4.66-5.01, spreadability 5.63-6.03 cm2, viscosity 8100-9100 cPs. The results of the stability cycling test did not show changes in organoleptic and pH of the preparation, while the viscosity of the preparation decreased. Penetration test results based on statistical analysis of purple leaf extract emulgel obtained p> 0.05, which means that the addition of aloe vera extract bioenhancer did not have a significant effect on the value of the cumulative amount and flux.Keywords: emulgel, bioenchancer, penetration, franz diffusion cell